Carnavalização como transgrediência da multidão - Silvestri, Kátia Vanessa Tarantini (2014)
Problematize the carnivalesque as a political inorganization a multitude of subjects who transgress power relations is the general aim of the thesis study. Popular demonstrations in societies that emerge are answers to the oppressor s mechanisms and relations of power that the capitalist logic promotes. These popular events appear as everyday ideology through carnivalesque relationships and are problematized, by this reflection, as objects of study. Two cutouts appear as places of observation in order to emphasize the clashes. 1) The street carnivals that reappear in the last ten years in the national and international scene as noted by the media dissemination. 2) The movement known as Carnival Against Capitalism - promoted by individuals from different countries constituting crowds that destabilize power relations. For such thinkers as Bakhtin (2006a, 2010a, 2010b, 2010c, 2011a ) and Negri, Hardt ( 2005a ) are crucial references in this architectural reflection. Some questions guide this study: 1) What can be read as manifestations carnival towards transgredient? 2) How different subjects do carnival? The purpose is specifically from such questions: 1) argue that every day events can carry a valued investment and such investment, disrupts discourses and relations of domination. 2) Affirm the existence of a "collective of a singularity which are not limited to the massive pocket of dough and composes the crowd. 3) Understand the crowd as a grotesque body - tireless and inalienable. Taking for granted the inextricable link between the social situation and the sign key understandings were: 1) There is no cohesive identity, but identities in constant struggle. 2) There is no speech that completely silenced the other, but lives in the discursive struggle linguistic materiality. 3) The carnivalization is a form of activism, a responsive activity. 4) A rule carnival happens as a counterpoint to the official system through various demonstrations and protests, art, music and parties. 5 - A crowd of singularities also has an affirmative view towards transgredient. Their actions may be carnival i.e., responses to ethics rectified. The research methodology is based on the theoretical perspective of Bakhtin's dialogical dialectic - clash of words and against words - which briefly means that the sign is part of a communication system and therefore cannot be separated from the concrete forms of communication, there is no separation between material reality and ideology of the sign, and there is a tense relationship between official and everyday discourses of.